Can left ventricle mass index predict pacemaker-induced cardiomyopathy in patients with dual chamber permanent pacemakers implanted due to complete atrioventricular block?. (3rd October 2022) - Hayiroglu, M; Cinar, T; Cinier, G; Yuksel, G; Pay, L; Keskin, K; Coskun, C; Ayan, G; Cicek, V; Tekkesin, A I
Abstract: Background: Pacing induced cardiomyopathy (PICM) occurs due to high-burden right ventricular pacing. In patients with complete atrioventricular (AV) block, it is presumed to have a higher burden of right ventricular pacing. There is a lack of data regarding the relationship between PICM and pre-implantation left ventricular mass index (LVMI). Purpose: This study aims to investigate the effect of LVMI on PICM in patients with implanted dual chamber permanent pacemakers (PPM) due to complete AV block. Methods: PPM implanted 577 patients were divided into three groups according to admission LVMI. Mean duration of follow-up was 57±38 months. The baseline characteristics, laboratory and echocardiographic variables were compared between the groups. The independent predictors of PICM incidence and the effect LVMI on PICM were evaluated. Results: Age, post-implantation QRS duration, left atrium anteroposterior diameter and LVMI were determined to predict long-term PICM. After adjustment for confounding baseline variables, tertile with highest LVMI had 1.9 times higher rates of long-term PICM compared to tertile with lowest LVMI, which was used as the reference group. A ROC analysis showed that the optimal cut-off value of the LVMI to predict long-term PICM was 109.8 mg/m 2 with 71% sensitivity and 62% specificity (AUC: 0.68; 95% CI: 0.60–0.76; p<0.001), Conclusion: Pre-implantation LVMI plays an important prognostic role in predicting PICM in patients with implanted dual chamber PPM due to complete AV block. Funding Acknowledgement: Type of funding sources: None.